2016
DOI: 10.11591/ijece.v6i2.9356
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Time Response of Power Plant Grounding System Exposed to Lightning Strike

Abstract: This paper examines the frequency response of power plant grounding system exposed to the lightning current. Large amount of current generated by the stroke flow in the grounding system of power plant and dissipate in the soil.  The electric and magnetic field generated by such high voltages and currents may cause damage of equipment and may be dangerous for the personnel in power plant.  For the every given frequency obtained using Fast Fourier Transformation (FFT) of lightning current impulse, electromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For example, CDEGS, which is a specialized program with high performance, can define the type of laydown materials, simulate 2 layers of such materials, and also give the illustrative results in 2-and 3-D formats, but it has disadvantage in high cost and requirement for very effective computer resources and operating systems. Apart from that, the fast Fourier transformation (FFT) program has been used for calculating the frequency and time response values and illustrating the magnetic fields in the case of lightning strike on power plant's ground grid [13]. Moreover, PSCAD program has been applied for analyzing the effects of induced voltage due to lightning strike on overhead transmission line that affecting below gas pipeline [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CDEGS, which is a specialized program with high performance, can define the type of laydown materials, simulate 2 layers of such materials, and also give the illustrative results in 2-and 3-D formats, but it has disadvantage in high cost and requirement for very effective computer resources and operating systems. Apart from that, the fast Fourier transformation (FFT) program has been used for calculating the frequency and time response values and illustrating the magnetic fields in the case of lightning strike on power plant's ground grid [13]. Moreover, PSCAD program has been applied for analyzing the effects of induced voltage due to lightning strike on overhead transmission line that affecting below gas pipeline [8].…”
Section: Resultsmentioning
confidence: 99%
“…Since CDEGS could show the results in three-dimensional (3D) illustrations and perform integration of frequency dependent soil electrical properties in grounding electrode circuit model, it was therefore used for examining the impacts of different soil resistivity levels, conductor materials, lightning impulse voltage front time waveforms, and soil profiles (uniform, 2-layer, and 3-layer) [8]- [12]. Interestingly, the use of CDEGS program could help to create the 3D plots of power plant's grounding system that was struck by lightning current and illustrate that the scalar potentials and electric fields were seriously affected [13]. In addition, the electrical transient analyzer program (ETAP) was used to optimize the similar parameters, especially the conductors' types, lengths, depths, and sizes [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…According to [1], lightning discharges are characterized by short duration of high electric voltage and current pulses. Also, lightning event is arbitrary, unpredictable and can strike anywhere on earth with current value that could exceed 40kA, induce temperature up to 50,000 degrees Fahrenheit, and move at speed closing to 33% speed of light [1], [2]. Lightning is the transient passage of electrical current between a cloud and either the surface of the earth, another cloud, or an object in or near a cloud.…”
Section: Introductionmentioning
confidence: 99%
“…Lightning strikes, especially C-G, has continued to be subject of studies in different locations and conditions as depicted in [2], [5], [7]- [9]; especially as it impacts protective grounding designs and locations; empirical intensities, physical processes in different geographical locations have been the foci. These mostly location specific foci and approaches are particularly central for sub-saharan Africa studies, where dependence on foreign models and technologies are predominant.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Current Distribution in Earth and Grounding System (CDEGS) program has been used for illustrating the three-dimentional (3D) plots ofpower plant grounding system that was exposed to the lightning current. The results suggested that the spatial distributions of the scalarpotentials and the electric fields werelargely affected [7]. In addition, the severity of lightning strikeon transmission line tower andnearby gas pipeline was explored by using Power System Computer Aided Design (PSCAD) and CDEGS programs, and CDEGS could give more precise results of the effect of soil structure on induced voltage [8].…”
Section: Introductionmentioning
confidence: 99%